PELAKSANAAN PROMOSI PAKET WISATA DI PT. WIDADIFA TOURS & TRAVEL PEKANBARU - Nst, Ade Khofifah; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Implementing promotions from Travel Bureaus is a way to attract as many people as possible to use or buy the products offered as well as to show the company's various products and attract public attention to the company's services. This research aims to find out the promotions carried out by PT. Widadifa Tours & Travel in order to increase sales of tour packages to reach sales targets and to find out the efforts made to increase the implementation of tour package promotions at PT. Widadifa Tours & Travel Pekanbaru. This research uses a qualitative method with a descriptive approach to describe and display the conditions that exist at the research location by collecting data and information obtained directly from the field. The key informants in this research are the Main Director, Accounting Staff and Ticketing Staff from PT. Widadifa Tours & Travel. In this research, the data collection techniques used were interviews, observation and documentation. From this research it can be seen that the promotion of services carried out by PT. Widadifa tours & Travel Pekanbaru is advertising, sales promotion, publication and personal selling. Of all the promotions carried out, publication information and personal selling are the promotions that have the most influence on product sales and purchases. However, it does not rule out the possibility that other promotions carried out will also have an influence on the sales products they offer. Keywords: Travel Agency, Promotion, PT. Widadifa Tours & Travel